LAW ENFORCEMENT AND PROTECTION OF NOTARIES IN THE CRIMINAL DOMAIN AND LAW OF NOTARY POSITION (CASE STUDY OF DECISION NUMBER 196/PID.B/2019/PN DENPASAR) - Gede Amatya Ananta; I Made Arjaya; Anak Agung Istri Agung (NOTARIIL Jurnal Kenotariatan, 2021)
Notary is an official authorized to make an authentic deed in accordance with the provisions of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Position of Notary (UUJNP). In carrying out his duties, the notary must uphold the moral values ​​and professional ethics and must obey the applicable law so as not to make mistakes which will carry risks for the notary himself and cause harm to the community. Risks arising from negligence for the notary public in their duties are in the form of enforcement of sanctions both civil sanctions, criminal sanctions and administrative sanctions. This study analyzes criminal enforcement of notaries, as well as norm conflicts that arise between criminal decisions by judges against notaries and the applicable laws. The aims of this study is to find out the enforcement and sanctions against notaries in the realm of criminal law and notary office law based on case study of decision number 196 / pid.b / 2019 / pn Denpasar), and to determine the form of legal protection against notaries. This study uses the normative juridical method. The results of this study revealed that there are two elements in law enforcement and protection of notaries, namely preventive and repressive. Preventive in the form of supervision of notary practices and repressively is the imposition of sanctions. The form of legal protection for notaries is carried out by the Notary Supervisory Board and the Notary Honorary Council.